Sustainable Gastronomy and Disaster Vulnerability in Majalengka District - Putri Dias Pratami; Bridha Risya Ladiva; Insani Hurry Mega; Hindayani Purna; Priatini Woro; Tsaniah Ilmiati (E3S Web of Conferences)
The study addressed sustainability and vulnerability in hazards in Majalengka District, focusing on the gastronomic sector. Sustainable gastronomy emphasizes environmental responsibility, social equity, and economic viability in food production until consumption. Sustainable gastronomic tourism is a crucial component of sustainable tourism development, but its durability may be compromised by a natural hazards. This study analyze the relationship between sustainable gastronomy and vulnerability to hazards in Majalengka District. The research involved mapping the distribution of culinary tourism places, vulnerability analysis, and stakeholder interviews. The method used is the Geographic Information System (GIS) method, assisted by the Global Positioning System (GPS), determine locations, with hazard data from INARISK. The results showed that the distribution of culinary tourism in Majalengka Regency is not always related to the level of vulnerability to natural hazards. The analysis revealed that gastronomic location is related to vulnerability to extreme weather disasters. Additionally, factors such as accessibility, risk planning and management, and community participation, play an important role in the sustainability of the gastronomic sector. This research is crucial for formulating sustainable tourism development strategies that consider hazard vulnerability, enhancing our understanding of sustainable gastronomic tourism’s potential to mitigate and adapt to natural hazards in Majalengka Regency.